Tapered Long Period Gratings - Mullaney, Kevin; James, Stephen W.; Staines, Stephen; Tatam, Ralph P. (Cranfield University, 2017)
OFS_2017_TLPG_Fig2.xlsx. Figure 2 from Proc. SPIE 10323, 10323C. The spectrum of a tapered long period grating after the fabrication of each of the tapered sections, where the waist diameter was 117 Î¼m and the period was of 418 µm. The TLPG was fabricated in Fibrecore SM750 fibre, and the spectrum recorded using an Ocean Optics CCD spectrometer. OFS_2017_TLPG_Fig3.xlsx. Figure 2 from Proc. SPIE 10323, 10323C. The transmission spectra of 3 TLPG, each comprising 6 tapered sections, with periods of 378,421 and 460 µm and duty cycles of 55, 45 and 41 %.
Keywords: optical fibre devices'; 'optical fibre sensors'; 'tapered optical fibres'; 'tapered optical fibre long period gratings'; 'Photonics and Electro-Optical Engineering (excl. Communications)'